Transhumanism, a paradigm for the analysis of living and housing post pandemic (2022)
At present, the paradigm of housing design and construction is approached under economic and environmental analysis schemes. However, this issue has fundamental risks, such as identifying the origin of the problem in essential aspects such as the conception of living and the way in which this action shapes spaces, systems of intervention and appropriation of the environment. The pandemic resulting from the covid-19 outbreak has generated circumstances in which confinement and social distancing regulations have made the limitations of the current paradigm evident in many aspects, particularly the design of housing being one of the most important. For this reason, this article aims to explore and analyze the modern housing paradigm, the problems that have emerged during the pandemic, and present a new paradigm based on the implementation of approaches that seek to explore options to redefine the human condition through knowledge and understanding. technology through concepts such as transhumanism which is proposed as an alternative to overcome the limitations and damages of the modern age; as well as avoiding the search for utilitarian absolutes in the field of the construction of human habitation